Pelatihan Perbendaharaan Gereja Jemaat GPM Rumahtiga Klasis Pulau Ambon Utara - Meiske Wenno (LPPM STIKOM Tunas Bangsa, 2022)
The goal this activity is to provide knowledge to to the treasurer of the church and the organization's service forum about the importance of financial records in church financial management. The approach technique used is seminars and simulations or direct exercises. It is hoped that this activity will have an impact of the GPM Rumahtiga Klasis congregation in North Ambon Island klassis, namely the improvement of church finances and the application of financial records to achieve financial management transparency.